Hydrogen Sulfide Promotes Surface Insertion of Hippocampal AMPA Receptor GluR1 Subunit via Phosphorylating at Serine‐831/Serine‐845 Sites Through a Sulfhydration‐Dependent Mechanism. (6th July 2016) - Li, Yuan‐Long; Zhou, Jun; Zhang, Hai; Luo, Yi; Long, Li‐Hong; Hu, Zhuang‐Li; Chen, Jian‐Guo; Wang, Fang; Wu, Peng‐Fei
Summary: Aims: Hydrogen sulfide (H2 S) has been widely accepted as a gas neuromodulator to regulate synaptic function. Herein, we set out to determine the effect of H2 S on α ‐amino‐3‐hydroxy‐5‐methylisoxazole‐4‐propionic acid receptor (AMPAR) and its mechanism. Methods: BS 3 protein cross‐linking, Western blot, patch clamp, and biotin‐switch assay. Results: Bath application of H2 S donor NaHS (50 and 100 μ M) rapidly promoted surface insertion of hippocampal AMPAR GluR1 subunit. This effect can be abolished by dithiothreitol (DTT) and mimicked by Na2 S4, indicating that a sulfhydration‐dependent mechanism may be involved. NaHS increased APMAR‐mediated EPSC and led to an elevation of GluR2‐lacking AMPAR content. Notably, NaHS did not increase the sulfhydration of AMPAR subunits, but it significantly increased the phosphorylation of GluR1 at serine‐831 and serine‐845 sites. Postsynaptic signal pathways that control GluR1 phosphorylation, such as protein kinase A (PKA), protein kinase C, and calcium/calmodulin‐dependent protein kinases II (CaMKII), were sulfhydrated, activated by NaHS, and these effects can be occluded by DTT. H2 S increased S‐sulfhydration of protein phosphatase type 2A (PP2A), which may be partially involved in the activation of signal pathways. Conclusion: Our data suggest that H2 S promotes surface insertion of AMPARs via phosphorylation of GluR1, which depends on a sulfhydration‐mediated mechanism.